Older Adults’ Conduct of Everyday Life After Bereavement by Suicide: A Qualitative Study - Hybholt, Lisbeth; Berring, Lene Lauge; Erlangsen, Annette; Fleischer, Elene; Toftegaard, Jørn; Kristensen, Elin; Toftegaard, Vibeke; Havn, Jenny; Buus, Niels (Frontiers in Psychology, 2020)
Background: The loss of a loved one to suicide can be a devastating experience that can have negative long-term effects on the social life and physical and mental health of the bereaved person. Worldwide, an estimated 237 million older adults have experienced suicide bereavement. As assumed in critical psychology, “the conduct of everyday life” reflects the social self-understanding by which people actively organize their lives based on their personal concerns, negotiation with co-participants in various action contexts, and their life interests. Bereaved people may change their social self-understanding as they adjust to their new roles and relationships in everyday life. The aim of this study was to investigate how older adults bereaved by suicide conducted their everyday life during the first 5 years after the loss of a loved one. Methods: This was a semi-structured qualitative interview study carried out by a research team consisting of co-researchers (older adults aged ≥60 years and bereaved by suicide), health care professionals, and researchers. The team conducted 15 semi-structured interviews with 20 older adults bereaved by suicide. The interviews were audio-recorded and verbatim transcribed. The participants’ mean age was 67.6 (range 61–79) years at the time of the loss. Data were thematically analyzed through a “conduct of everyday life” theoretical perspective. Results: We constructed a central theme “the broken notion of late-life living” in that late-life would no longer be as the participants had imagined. They struggled with their understanding of themselves and other people in social communities when they pursued their concerns adjusting to their broken notions of late-life living. We construed three primary concerns: 1) seeking meaning in the suicide, 2) keeping the memory of the deceased alive, and 3) regaining life despite the loss. Conclusion: The participants’ bereavement process was influenced by their stage in life. They perceived themselves as having reduced possibilities to restore their life project and limited time to re-orient their life. Other age-related factors influenced their possibilities to pursue their concerns in order to adjust to their new life conditions.